A memory system of negative polarity cues prevents replicative aging - Meitinger, Franz; Khmelinskii, Anton; Kurtulmus, Bahtiyar; Palani, Saravanan; Knop, Michael; Pereira, Gislene (Cell, 2014)
Summary Cdc42 is a highly conserved master regulator of cell polarity. Here, we investigated the mechanism by which yeast cells never re-establish polarity at cortical sites (cytokinesis remnants [CRMs]) that have previously supported Cdc42-mediated growth as a paradigm to mechanistically understand how Cdc42-inhibitory polarity cues are established. We revealed a two-step mechanism of loading the Cdc42 antagonist Nba1 into CRMs to mark these compartments as refractory for a second round of Cdc42 activation. Our data indicate that Nba1 together with a cortically tethered adaptor protein confers memory of previous polarization events to translate this spatial legacy into a biochemical signal that ensures the local singularity of Cdc42 activation. “Memory loss” mutants that repeatedly use the same polarity site over multiple generations display nuclear segregation defects and a shorter lifespan. Our work thus established CRMs as negative polarity cues that prevent Cdc42 reactivation to sustain the fitness of replicating cells.